2007
DOI: 10.1007/s10389-006-0085-x
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in public health: a formal and content-related analysis of European journals

Abstract: Staphylococci are ubiquitous microorganisms that predominate in normal skin and mucosal flora. Staphylococcus aureus and Staphylococcus epidermidis have been identified as a major cause of nosocomial infections, especially in patients with predisposing factors such as indwelling or implanted foreign bodies. The ability of both S. epidermidis and S. aureus to produce biofilm was compared between 116 clinically significant strains (46 from blood cultures of patients with bloodstream infection and 70 isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…Likewise, in a collection of strains causing catheter-related urinary infections, 88.6% were biofilm-producers and all of them expressed the ica locus16. In this context, an Argentinian study showed that 35% of strains collected in nasal swabs from hospitalized patients or from staff are ica -positive and that all were slime producers56. Conversely, ica -negative strains producing slime have been rarely described in S. aureus infection57, underlining the interest of detecting icaA expression in clinical isolates prior using inhibitors of IcaA as adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in a collection of strains causing catheter-related urinary infections, 88.6% were biofilm-producers and all of them expressed the ica locus16. In this context, an Argentinian study showed that 35% of strains collected in nasal swabs from hospitalized patients or from staff are ica -positive and that all were slime producers56. Conversely, ica -negative strains producing slime have been rarely described in S. aureus infection57, underlining the interest of detecting icaA expression in clinical isolates prior using inhibitors of IcaA as adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cramton et al [14] demonstrated the presence of icaA gene in S. aureus strains, which was confirmed by Arciola et al [1] describing 23 S. aureus starins isolated from 14 catheter associated infections with the ability to form slime layer based on te presence of the gene icaA, but also icaD . Indeed, while icaA is required to encode N-acetylglucosaminyltransferase, coexpression of icaD can increase the capsular polysaccharide phenotypes [15], indicating a significant role of the icaD locus as a virulence factor in the pathogenesis of S. aureus isolated from catheters [13], [16]. …”
Section: Discussionmentioning
confidence: 99%
“…The isolates of S. aureus were characterized as described previously (Satorres and Alcaráz, 2007). The interpretation of coagulase test was performed according to Sperberg and Tatini (1975).…”
Section: Methodsmentioning
confidence: 99%